Blood work [videorecording (DVD)] - Eastwood, Clint, 1930-; Daniels, Jeff, 1955-; De Jesús, Wanda; Lifford, Tina; Connelly, Michael, 1956- (Warner Home Video, 2002)
There is a masked killer on the loose, and the police believe its the locations that are important and that the victims are just unlucky. But retired FBI agent McCaleb thinks that it goes the other way around. The killer's victims are very specific. Forced to retire after suffering a heart attack, and receiving a new heart 2 years later, he is approached by the sister of the murdered woman whose heart he now has. Now McCaleb has to use his wits to discover who is responsible for the murders.